Faktor-Faktor Yang Mempengaruhi Integritas Jaksa Dalam Penuntutan Tindak Pidana - Taqwallah, Andri Nurwandri, Abzha Aufa, Alfata Dinata, Hery Sistama, (Pusdikra Publishing, 2024)
The purpose of this study is to identify the variables that affect prosecutors' moral character when they bring criminal charges. Consequently, one factor that affects both the system's and law enforcement's efficacy is law enforcement. Integrity is a crucial principle that prosecutors, as law enforcement officials, must uphold at all times. Building integrity as an ethical character that preserves value principles requires a thorough methodology. This is consistent with the numerous instances of corruption that have occurred, which demonstrate the prosecutor's lack of integrity. The author balances legal culture, which is an intrinsic component of law enforcement, and uses this to guide the process of looking for a formula for establishing integrity. This essay employs qualitative research techniques using case, legal.